Structural, mechanical, and thermal properties of 3D printed L‐CNC/acrylonitrile butadiene styrene nanocomposites. Issue 31 (20th April 2017) - Feng, Xinhao; Yang, Zhaozhe; Rostom, Sahar S. H.; Dadmun, Mark; Xie, Yanjun; Wang, Siqun
ABSTRACT: 3D printing has been extensively applied in human‐related activities, and therefore the 3D printed nanocomposites became more popular and important in end‐use products. In the present study, we use lignin‐coated cellulose nanocrystal (L‐CNC) to reinforce 3D printed acrylonitrile butadiene styrene (ABS) and explore the effect of L‐CNC on the structural, mechanical, and thermal properties of 3D printed L‐CNC/ABS nanocomposites. The results indicate that the addition of L‐CNC foams the ABS and decreases the density of 3D printed L‐CNC/ABS nanocomposites. However, the tensile modulus and storage modulus increase by adding 4% L‐CNC. The thermal stability of 3D printed L‐CNC/ABS nanocomposites is also significantly improved as indicated by an increase in the maximum degradation temperature. The morphology of the nanocomposites reveals good dispersion and interfacial adhesion between L‐CNC and ABS. The finding indicates that the 3D printed nanocomposites become lighter and stiffer with addition of L‐CNC, which will have great potential to be applied in end‐use products. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45082. Abstract :